Grapevine virome and production of healthy plants by somatic embryogenesis. Issue 5 (19th February 2022) - Nuzzo, Floriana; Moine, Amedeo; Nerva, Luca; Pagliarani, Chiara; Perrone, Irene; Boccacci, Paolo; Gribaudo, Ivana; Chitarra, Walter; Gambino, Giorgio
Summary: Grapevine ( Vitis spp.) is a widespread fruit tree hosting many viral entities that interact with the plant modifying its responses to the environment. The production of virus‐free plants is becoming increasingly crucial for the use of grapevine as a model species in different studies. Using high‐throughput RNA sequencing, the viromes of seven mother plants grown in a germplasm collection vineyard were sequenced. In addition to the viruses and viroids already detected in grapevine, we identified 13 putative new mycoviruses. The different spread among grapevine tissues collected in vineyard, greenhouse and in vitro conditions suggested a clear distinction between viruses/viroids and mycoviruses that can successfully be exploited for their identification. Mycoviruses were absent in in vitro cultures, while plant viruses and viroids were particularly accumulated in these plantlets. Somatic embryogenesis applied to the seven mother plants was effective in the elimination of the complete virome, including mycoviruses. However, different sanitization efficiencies for viroids and grapevine pinot gris virus were observed among genotypes. The absence of mycoviruses in in vitro plantlets, associated with the absence of all viral entities in somaclones, suggested that this regeneration technique is also effective to eradicate endophytic/epiphytic fungi, resulting in gnotobiotic or pseudo‐gnotobiotic plants. Abstract : The production of virus‐free plants is becoming increasingly crucial for the use of grapevine as a model species in different studies. The different spread among grapevine tissues suggested a clear distinction between viruses/viroids and mycoviruses that can successfully be exploited for their identification. Somatic embryogenesis was effective in the elimination of the complete virome, including mycoviruses.